AB0793 Descriptive analysis of a cohort of patients diagnosed with inflammatory myositis in a tertiary hospital. (12th June 2018) - Ibarguengoitia, O.; Ruiz, E.; García, M.L.; Kapetanovic, S.; Fernández, O.; Torre, I.; Inchaurbe, A.R.; Pérez, C.; Blanco, J.M.; Calvo, I.; Guerrero, E.; Montero, D.; et al.
Abstract : Background: Inflammatory myopathies are a group of rare systemic diseases characterised by muscle weakness and inflammation. Clinical manifestations, course and prognosis of these patologies are very heterogeneous. Objectives: The aim is to describe the main characteristics of patients diagnosed with inflammatory myositis fulfilling Bohan and Peter criteria. Methods: Descriptive analysis of a cohort of 34 patients from the same hospital with follow-up between January 2010 and December 2017. We recorded demographic characteristics, clinical manifestations, treatment, comorbidity and mortality. Results: 34 patients (73% female) were recruited with an average age at diagnosis of 56.3 years 27–83 among adults and 10 years 4–15 among children. Most of them were Caucasian (94%). 18% were smokers and 15% previous smokers. The most frequent type was dermatomyositis (DM) (40%) followed by antisynthetase syndrome (ASS) (15%), necrotizing myopathy (12%), inclusion body myopathy (12%), overlap myositis (9%) and polymyositis (9%). 2 patients (out of 4) with necrotizing myopathy were treated with statins. Clinical manifestation included muscle weakness (84%) and skin manifestations (48%) mainly among DM patients. 8 patients (24%) showed interstitial lung disease (4 non-specific interstitial pneumonia, 3 usual interstitial pneumonia and 1 cryptogenic organising pneumonia), especially among patients with overlap syndrome (n=3), DM (n=2) and ASS (n=2). Pulmonary hypertension occurred in 7 patients (21%), 30% among patients with overlap myositis associated to systemic sclerosis. The rest of extramuscular manifestations are expressed in the table 1. Muscle biopsy was performed in 57% of patients (77% compatible with myopathy). MRI was carried out in 45% (100% with active myositis). EMG was performed in 94% of patients with myopathic findings in 67% of them. 20 patients (60%) presented positive antinuclear antibodies, being the most frequent antiPML-SCL (18%), antiJo1 (18%), antiRo (12%) and anti-MDA5 (9%). All patients were treated with corticosteroids. Only 2 responded to corticosteroids in monotherapy. More than 90% needed additional immunosuppressive treatment and 65% received 2 or more immunosuppressants. The most commonly used drugs were methotrexate (72%), rituximab (28%), azathioprine (25%), immunoglobulins (21%) and cyclophosphamide (21%). Only in 12% treatment could be stopped because of sustained remission. 3 cases of cancer (9%) were reported: myelodysplastic syndrome, lung neoplasm (in the case of paraneoplasic myositis) and lymphoma. During the follow-up period 4 deaths were registered (12%) due to infections and cancer. 38% of patients required a multidisciplinary approach. Conclusions: Inflammatory myopathies have frequent multiorganic involvement and represent a heterogeneous group of systemic diseases as shown in our registry and in the literature. Most patients need chronically combined immunosuppressive treatment and few achieve sustained remission. In consequence the collaboration of several specialties is necessary for the diagnosis and management of these pathologies. Reference: [1] Nuño L, et al. Multicenter registry on inflammatory myositis from the Rheumatology Society in Madrid, Spain. Reumatol Clin2017; 13(6):331–337 Disclosure of Interest: None declared